The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0038040719839100
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Third Spaces: Exploring Trans Students’ Campus Climate Perceptions Within Collegiate Environments

Abstract: Our study aims to understand trans students' perceptions of campus climate, with a particular focus on students' demographics, academic experiences, and cocurricular experiences. We use Bhabha's concept of third space as an epistemological lens and Rankin and Reason's transformational tapestry model as a theoretical framework. Using a national sample of 207 trans collegians from the National LGBTQ Alumnx Survey, we utilize regression analysis supplemented by an analysis of open-ended responses to highlight the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Using a microclimates framework, we can see how trans people's experiences of disclosure vary intrainstitutionally. At the university level, name‐change and nondiscrimination policies present different possibilities and risks of disclosure; even if someone does not use a policy, its presence can serve a symbolic purpose (Garvey, Viray, Stango, Estep, & Jaeger, ). Scholars may feel more or less comfortable disclosing in a given department based on its perceived climate, which varies.…”
Section: Disclosing Trans Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a microclimates framework, we can see how trans people's experiences of disclosure vary intrainstitutionally. At the university level, name‐change and nondiscrimination policies present different possibilities and risks of disclosure; even if someone does not use a policy, its presence can serve a symbolic purpose (Garvey, Viray, Stango, Estep, & Jaeger, ). Scholars may feel more or less comfortable disclosing in a given department based on its perceived climate, which varies.…”
Section: Disclosing Trans Identitiesmentioning
confidence: 99%
“…Microclimates can also shift based on visible leadership and attendance. For example, perceived social cliques or a lack of representation can be alienating (Garvey et al, ).…”
Section: Transgender Communities: Too Trans or Not Trans Enough?mentioning
confidence: 99%
“…Academic and social spaces are important to promote identity development and success among QT students because they foster connections with QT and allied faculty, staff, and peers. Garvey, Viray, et al (2019) found that trans students' interpersonal interactions with peers are central to their climate perceptions and identity disclosure. There is also a clear connection between outness and positive relationships with faculty and mentors (Garvey & Inkelas, 2012).…”
Section: Identity Developmentmentioning
confidence: 98%
“…Nicolazzo and Marine (2015) noted that QT institutional supports and policies often center LGBQ students and may not equally serve trans students. Creating services that center trans students can help build a sense of belonging, which in turn can foster success and persistence (Garvey, Viray, Stango, Estep, & Jaeger, 2019). QT resource centers are of critical importance for QT students of color because they provide "forums to mobilize and opportunities to create community and engage vital discourses surrounding LGBTQ issues on their respective campuses" (Garvey, Mobley, et al, 2019, p. 169).…”
Section: Qt Student Servicesmentioning
confidence: 99%
“…Despite sociological attention to transgender individuals within organizational structures including the workplace, the family, health care, and the criminal justice system, there is a noticeable dearth of sociological literature that centers transgender identity within postsecondary education (c.f. Garvey, Viray, Stango, Estep, & Jaeger, 2019). Most extant research over-relies upon "campus climate" studies for LGBTQ+ students.…”
Section: Thinking Sociologically About Transgendermentioning
confidence: 99%